They who know not what the media is - Rattanani, Jagdish (Economic and Political Weekly)
Many in India are lamenting the hostile takeover of NDTV by the Adani Group. At one level, this is a desperate attempt to silence the voices that stand out as independent in today$1 (Bs increasingly controlled media space. But what really will be gained by one more channel singing the official tune? It, of course, controls criticism of the government, but it will also signal that the future of the media may not be in large enterprises that give in or get taken down rather easily.- Reproduced s
Keywords: Media